Management of a Rare Case of Firecracker Thoracic Injury with Empyema - Prashant Kothari; Rajat Piplani; Poonam Sherwani; Yogendra Kumar Yogesh; Vyas Kumar Rathaur (Journal of Indian Association of Pediatric Surgeons)
Firecracker thoracic injuries are rare but critical, often requiring multidisciplinary management. We report a case of a teenage male patient who presented with hemothorax and empyema due to a firecracker-related chest wall injury. Initial management involved tube thoracostomy; however, the patient subsequently required thoracoscopic intervention for the removal of intrathoracic firecracker residue and decortication. This case emphasizes the significance of early intervention, tailored antibiotics, residue removal for recovery, and preventive measures for such injuries.